Gastrointestinal Symptoms and Hepatopancreatic Involvement in COVID-19 Children: A Narrative Review - Sanaz Mehrabani; Maryam Nikpour; Leila Moslemi (Mazandaran University of Medical Sciences, 2022)
Background: To the best of our knowledge, limited studies explored gastrointestinal (GI) symptoms and hepatopancreatic involvement in children with coronavirus disease 2019 (COVID- 19) infection.  Objectives: This review study aimed to evaluate the GI symptoms and abnormal liver and pancreas function in children with COVID-19 infection. Methods: In this review study, databases of Scopus, PubMed, Google Scholar, and Web of Science were searched using the relevant keywords of "COVID-19," "children," "gastrointestinal," "liver," and "pancreas." Descriptive and cross-sectional studies were reviewed in the current study, with the main focus on GI symptoms and elevated liver enzymes in children with COVID-19 infection.  Results: Overall, 27 studies from countries of Iran, Spain, Turkey, Italy, and the United States were selected. Although the prevalence of GI symptoms varied in different studies, our review showed that most children with COVID-19 infection experienced GI symptoms. In addition to GI symptoms, there is the possibility of elevated liver enzymes, such as alanine aminotransferase, aspartate aminotransferase, lactate dehydrogenase, and creatine phosphokinase in children with COVID-19 infection.  Conclusions: COVID-19 infection may present various GI, hepatic, and pancreatic manifestations in children. The difference in the prevalence of these symptoms can probably be attributed to the geographical region of the study and the history of the disease.